Professional Development Through MOOCs in Higher Education Institutions: Challenges and Opportunities for PhD Students Working as Mentors. Issue 1 (21st December 2016) - Urrutia, Manuel León; Fielding, Sarah; White, Su
The advent of Massive Open Online Courses (MOOCs) has been altering the Higher Education landscape in recent years. This kind of courses are penetrating in an increasing number of universities, the majority of which do not seem to have intentions to stop offering them in the short term. Such courses are generating new educational scenarios to which universities have to adapt, which creates a set of challenges and opportunities, most of them related to the use of technology in education. This study aims to shed light on such challenges and opportunities when a university employs postgraduate students as MOOC mentors. For this study, a set of focus group interviews were conducted in an English university to PhD students in various disciplines. In the interviews, participants share their experiences as mentors, especially regarding how they developed certain teaching and digital skills, and how they faced certain challenges related to their digital identity. The results suggest that participating in MOOCs as mentors can help early career researchers to develop certain teaching, digital, and academic skills that could be beneficial for the institutions they work for, and for themselves. However, their online exposure sometimes raises certain implications for their public image, their working conditions, and their online professional identity.